Acute and delayed impairments of muscle function after a sprint training session performed at different exercise regimens - Dal Pupo, J.; Kons, R. L.; Barth, J.; Ache-Dias, J. (Sport Sciences for Health, 2021)
Aim The study investigated the acute and delayed impairments of muscle function after a sprint interval training (SIT) session performed at two exercise regimens (continuous vertical jumps and cycling).